Issues Arising from the Rapid Growth of Mainland Chinese Visitors to Hong Kong: Implications for Tourism Marketing. Issue 3 (1st October 2016) - Tse, Tony S. M.; Qiu, Hanqin
ABSTRACT: The rapid growth of mainland Chinese visitors to Hong Kong has made economic contributions but also created various concerns and conflicts within the destination. As Hong Kong is at the forefront of mainland Chinese visitors' destinations, what happens in the city could serve as good reference for other destinations that would like to welcome more Chinese visitors. This study used a quantitative survey method to analyze the local community's attitude toward mainland Chinese visitors. A telephone survey was carried out to gauge Hong Kong residents' view towards visitors in general and mainland Chinese visitors in particular. Implications for travel and tourism marketing are drawn.